(untitled) (Vietnam Journal of Community Medicine, 2024)
Overview: Chronic limb-threatening ischemia (CLTI) due to atherosclerotic peripheral artery occlusion presents a significant clinical challenge, with high mortality and limb loss risks if not treated effectively. Advances in medical management, endovascular interventions, and surgical approaches have offered various treatment options, ranging from controlling risk factors to direct revascularization procedures. Vascular reconstruction surgery, particularly arterial bypass, has played and continues to play a central role in managing complex vascular lesions where endovascular approaches, such as angioplasty and stenting, are limited. While endovascular intervention has become increasingly popular due to its minimally invasive nature, surgery remains an important option for extensive occlusions or in cases where endovascular treatment fails. The role of surgery in an optimal treatment strategy is irreplaceable, especially for patients at high risk of limb loss, ensuring effective and durable revascularization. Clinical case: A 55-year-old male patient with a history of hypertension, diabetes mellitus, and prolonged smoking presented with lower limb pain and a non-healing ulcer. Doppler ultrasound and computed tomography angiography revealed occlusion of the common femoral artery and the popliteal-tibial arteries on the left side. After thorough evaluation, femoral-anterior tibial-posterior tibial bypass surgery was prioritized due to the complexity of the lesions that made endovascular intervention impractical. The surgery was successful, achieving complete revascularization, resulting in significant improvement in symptoms and ulcer healing. This case highlights the crucial role of surgery in managing complex vascular lesions while ensuring long-term and sustainable outcomes. Conclusion: Chronic limb-threatening ischemia is a complex condition requiring a multimodal treatment strategy. Endovascular intervention has become the first-line choice in many cases; however, vascular reconstruction surgery remains a crucial option for severe lesions or failures of endovascular treatment. Optimizing treatment requires careful assessment of the patient’s condition to minimize complications and improve quality of life.